Smoking cessation services for health staff: Experiences of a university hospital in Izmir, Turkey - Raika Durusoy (Tobacco Induced Diseases, 2018)
Aim and objective Our aim was to explore possible changes in the ratio of a university hospital’s health professionals among patients applying to the smoking cessation clinic situated inside the same hospital and to compare the characteristics and procedure of these applicants with other cessation service users.